2021
DOI: 10.3233/jad-210138
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Thickness and Its Association with Clinical Cognitive and Neuroimaging Markers in Cerebral Amyloid Angiopathy

Abstract: Background: Cerebral amyloid angiopathy (CAA) contributes to brain neurodegeneration and cognitive decline, but the relationship between these two processes is incompletely understood. Objective: The purpose of this study is to examine cortical thickness and its association with cognition and neurodegenerative biomarkers in CAA. Methods: Data were collected from the Functional Assessment of Vascular Reactivity study and the Calgary Normative Study. In total, 48 participants with probable CAA, 72 cognitively no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…Cerebral amyloid angiopathy (CAA) is a disease where vascular and AD pathologies coexisted. Studies have found that CAA could lead to cognitive decline, which might be achieved by reducing the thickness of the cortex (Subotic et al, 2021 ). A lot of anti-Aβ drugs were proposed but failed in clinical trials, so it is urgent to find new treatments to prevent AD progression in the early stage (Long and Holtzman, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral amyloid angiopathy (CAA) is a disease where vascular and AD pathologies coexisted. Studies have found that CAA could lead to cognitive decline, which might be achieved by reducing the thickness of the cortex (Subotic et al, 2021 ). A lot of anti-Aβ drugs were proposed but failed in clinical trials, so it is urgent to find new treatments to prevent AD progression in the early stage (Long and Holtzman, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Data were obtained from two referral‐based prospective observational studies: (1) Functional Assessment of Vascular Reactivity (FAVR), 22 and (2) Comprehensive Assessment of Neurodegeneration and Dementia (COMPASS‐ND). 23 …”
Section: Methodsmentioning
confidence: 99%
“…Recently, Subotic et al. demonstrated that CAA was associated with lower cortical thickness than that in controls and that the lower cortical thickness was associated with lower memory scores 31 . In addition, cases of CAA with an amnestic presentation tended to have a smaller hippocampal volume than their non‐amnestic counterparts 32 .…”
Section: Discussionmentioning
confidence: 99%